Penguatan Kesiapan Calon Manajer KDKMP Melalui Pelatihan Model Bisnis dan Manajemen Pemasaran Berkelanjutan di Rindam I/Bukit Barisan - Ati Atul Quddus; Rini Nur' Azizah (E-Coops-Day : Jurnal Ilmiah Abdimas, 2026)
The Merah Putih Village/Sub-district Cooperative (KDKMP) places managerial readiness as the main prerequisite for business units to be managed professionally, oriented towards member needs, and sustainably. This community service activity aims to strengthen the capacity of prospective KDKMP managers in mapping business models, designing business mentoring and communication strategies, and developing marketing management for sustainable businesses. The activity was carried out on July 17, 18, and 20, 2026 at Rindam I/Bukit Barisan, North Sumatra, as part of a 15-day class briefing, targeting 80 prospective C3A (S02) class managers who are a combination of two platoons. The community service method uses a participatory approach based on andragogy through concept presentations, case study discussions, worksheet completion, group presentations, and facilitator feedback, with a focus on Module IV on business models, business mentoring, and communication strategies, and Module V on marketing management for sustainable businesses. Evaluation is carried out descriptively through session implementation, discussion participation, worksheet completion, and portfolio readiness of assignments as provisions for competency tests by KDKMP assessors. This activity resulted in an initial draft of a business model, a stakeholder map and communication strategy, and a marketing plan that can be tailored to the local potential of each placement area. Case-based learning and worksheets proved relevant for strengthening the cognitive, affective, and conative aspects of prospective managers, but their success in the field remains dependent on continued post-placement mentoring and structured business performance measurement.